FEATURES OF THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES TO SUPPORT PROJECT PROCESSES IN DISTRIBUTED TEAMS - VASKIV, Roman; VERETENNIKOVA, Nataliia (Computer systems and information technologies, 2023)
The study presents an in-depth analysis of the role of information and communication technologies (ICT) in the context of managing project processes in distributed teams. The main focus is on the classification and evaluation of the effectiveness of communication and information technologies as tools that significantly increase productivity and contribute to the optimization of work processes in such distributed teams. The main interpretations of the concept of distribution in project teams are given. The methodological approach of the article is based on a comprehensive analysis of existing problems of communication and information exchange in distributed teams. A systematic approach was used to structure and define the main channels of communication, based on a hierarchical diagram developed on the basis of expert assessments and analysis of work processes. The results of the study present a detailed comparative analysis of widely used platforms for project management, such as Trello, Asana, Jira, Microsoft Project, etc., with an emphasis on their functionality, areas of application, and project management models and assignments in terms of distribution in project teams. The authors carried out a comprehensive comparison of communication and information systems, as a result, a number of main trends in the use of ICT in project management over the past four years were revealed. Special attention is paid to the most popular tools, the definition of their unique features and the potential of application in various projects. Innovative approaches to the automation of project processes in the context of project management platforms for distributed teams are also considered, with the proposal of a new algorithm for their implementation. The conducted analysis makes an important contribution to the understanding of how information and communication technologies can be applied to improve the efficiency and productivity of distributed teams, in particular in the aspects of supporting project processes. The study contributes to a deep understanding of the key factors affecting the successful integration of the considered technologies into modern project practices.